Teaching English Using AnActivity Based EFL Drama Course - Esti Ambaratsari (Universitas Bengkulu, 2017)
This paper aims at emphasizing the use of an activity-based EFL drama course as a popular technique for teaching both basic language skills (i.e. reading, writing, listening and speaking) and language areas (i.e. vocabulary, grammar and pronunciation) in our times by creating a suitable context. Drama is a powerful language teaching tool that in volves all of the students interactively all of the class period. Drama can also provide the means for connecting students’ emotions and cognition as it enables students to take risks with language and experience the connection between thought andaction. Teaching English as a foreign language in evitably in volves abalance between receptive and productive skills; here drama can effectively deal with this requirement. Through drama, a class will address, practice and integrate reading, writing, speaking and listening. Drama also fosters and maintains students’ motivation, by providing an atmosphere whichis full of fun and entertainment. In so doing, it engages feelings and attention and enriches thel earners' experience of the language.Kata Kunci: EFL drama class, Dramatic activities, Teachinglanguage skills